Statistical and Managerial Techniques for Six Sigma Methodology : Theory and Application - Barone, Stefano; Franco, Eva Lo. (Chicester : John Wiley & Sons, 2012)
Statistical and Managerial Techniques for Six Sigma Methodology examines the methodology through illustrating the most widespread tool and techniques involved in Six Sigma application. Both managerial and statistical aspects of Six Sigma will be analyzed, allowing the reader to apply these tools in the field. This book offers an insight on variation and risk management, and focuses on the structure and organizational aspects of the Six Sigma projects. It covers six sigma methodology, basic managerial techniques, basic statistical techniques, methods for variation and risk management and advanc.
Six sigma methodology -- Basic managerial techniques -- Basic statistical techniques -- Advanced managerial techniques -- Advanced statistical techniques -- Six sigma methodology in action: selected black belt projects in swedish organizations.
Includes bibliographical references and index.
Print version record.
Keywords: Total quality management; Quality control -- Management; Six sigma (Quality control standard); Management; BUSINESS & ECONOMICS -- Quality Control; BUSINESS & ECONOMICS -- Total Quality Management; Quality control -- Management; Six sigma (Quality control standard); Total quality management; Electronic books; Electronic books